BIBLIOMETRIC ANALYSIS OF ARTICLES CONTAINING ACCOUNTING RECORDS IN JOURNALS IN THE DERGIPARK SYSTEM IN TUKIYE (Third Sector Social Economic Review, 2023)
In this study, a detailed analysis was made of articles containing accounting records published in academic journals in Turkey between 2010 and 2022. In this context, the study aims to reveal the past and present structure of the field and to determine the article and journal performances and research components. The data used in the study was obtained from the DergiPark platform, which is the largest platform where academic journals are gathered together in Türkiye. In the DergiPark system, articles related to accounting records were identified by searching the words ""accounting record"", ""accounting"", ""accounting"" and ""accounting"" in the title, abstract and keywords. Bibliometric analysis method was used in the study and the data were collected through document analysis and analyzed through content analysis. In this context, a total of 343 articles were analyzed. According to the results of the study, it was determined that the most studies were conducted in 2020 and the least studies were conducted in 2010. In addition, it was determined that the institution with the highest number of researchers is Marmara University and the journal with the highest number of articles published is Accounting and Finance journal. It was observed that there was no systematic increase or decrease in the number of studies over the years. Considering the increase in the number of academic studies in recent years, it can be stated that the number of studies on accounting records is low. It is also noteworthy that most of the researchers are male and the number of female researchers in the field is quite low.
Keywords: Accounting Entry; Accounting; Accountancy Bibliometric Analysis